Zircon U–Pb, Lu–Hf and O isotopes from the 3414 Ma Strelley Pool Formation, East Pilbara Terrane, and the Palaeoarchaean emergence of a cryptic cratonic core - Gardiner, Nicholas; Wacey, D.; Kirkland, Chris; Johnson, Tim; Jeon, H. (Elsevier BV, 2019)
The detrital zircon record yields important information on crustal evolution that may be missing from extant magmatic rocks. The Palaeoarchaean to Neoarchaean East Pilbara Terrane (EPT), Western Australia, is the ancient core of the Pilbara Craton, and the archetypal granite-greenstone terrane. Magmatic zircon U–Pb crystallization ages from the EPT record crustal magmatism spanning 3.53–3.22 Ga. However, detrital zircons with ages as old as 3.65 Ga have been identified in EPT supracrustal sequences, which may provide key insights into the EPT's early Archaean history. The Strelley Pool Formation (SPF), one of the earliest EPT siliciclastic sedimentary successions, is a critical unit in the field of Precambrian palaeobiology, containing multiple lines of evidence for some of Earth's earliest life forms. The SPF was deposited on a continental shelf in a shallow water environment, upon perhaps the oldest preserved terrestrial erosion surface on Earth; it thus provides a record of a newly-emergent Palaeoarchaean continent. We report U–Pb, Lu–Hf and O isotope data from a suite of detrital zircon crystals sourced from the type locality of the SPF. Two hundred and five U–Pb detrital zircon analyses were undertaken via SIMS and LA–ICPMS. Four analyses define a young age peak of 3414 ± 34 Ma (2s), which we interpret as a maximum depositional age. Zircon Hf isotope analyses yield eHfi of -3.5 to +5.2, clustering around chondritic values, with two-stage Hf crustal model ages of 3.9–3.5 Ga. Zircon O isotopes give a range in d18O values from mantle-like (5.3‰) to more elevated (~6.4‰). Taken together, the Hf and O isotope record, from new and published detrital and magmatic zircon crystals, implies a juvenile (mafic) source for evolved rocks of the EPT until ca. 3.3 Ga, after which time it experienced a period dominated by reworking of existing crust, possibly reflective of a change in geodynamics. The relationship between the cryptic core of the EPT, which is perhaps as old as 3.8–3.7 Ga, and the extant magmatic rocks that comprise the exposed Palaeoarchaean granite domes, remains uncertain.